Pemetaan Bibliometrik Perkembangan Penelitian Biofilik di Indonesia - Ratnasari, Anisza; Dwisusanto, Yohanes Basuki (ALUR :Jurnal Arsitektur, 2024)
Biophilic design, which focuses on integrating natural elements into the built environment, has developed from the biophilia hypothesis. Currently, biophilic research has expanded into various fields. This literature review using bibliometric analysis aims to explore the trends of biophilic research in Indonesia. Data was collected through Publish or Perish for the period 2014-2024. VOSviewer was used for scientific mapping, while Lens.org was used for performance analysis. The results indicate that publications in scientific journals have increased over the past 5 years. Author mapping indicates some researchers are highly productive but show no co-authorship correlation. Meanwhile, mapping based on keywords depicts the dominance of research in the fields of design, architecture, and sociology. Recently, biophilic research in Indonesia has still focused on the implementation and evaluation of biophilic concepts in design, so that it is possible to open up opportunities for research collaboration in the fields of psychology, health, and ecology.